Health seeking behaviours, dengue prevention behaviours and community capacity for sustainable dengue prevention in a highly dengue endemic area, Sri Lanka - R. M. Nayani Umesha Rajapaksha; Chrishantha Abeysena; Aindralal Balasuriya (BMC, 2023)
Abstract Introduction Dengue has become a major health problem in globally as well as locally. The delay in health-seeking is significantly associated with complications leading to severe dengue and active engagement of communities needs to minimize the delays in management to control epidemics. The aim of the study was to evaluate the relationship between sociodemographic characteristics and householders' Health-Seeking Behaviours (HSB), Dengue-Prevention Behaviours (DPB), and Community Capacities (CC) for sustained dengue prevention in Sri Lanka, a country with a high dengue endemicity. Methods A cross-sectional analytical study was carried out in a district with the highest dengue endemicity from January to April 2019. Of the householders, 532 were chosen randomly. A pre-tested, validated, and interviewer-administered questionnaire was used to assess HSB and DPB. The HSB was assessed using three aspects, initial response for fever management, the duration of blood testing and initial response if suspected dengue. The DPB assessment was evaluated using 'waste, outdoor water container, indoor water container, roof gutter and water storage management'. 'Dengue Community Capacity Assessment Tool', with 14 key items was used to assess the level of community capacity for dengue prevention. Out of the total, ≥ 50% was considered as an "adequate" HSB, DPB and CC. Multiple logistic regression was performed to control confounding effects. The results were expressed as adjusted Odds-Ratios (aOR) and 95% Confidence Intervals (CI). Results The response rate was 93.2% (n = 496). Among them, 44.6% (n = 221) had adequate overall HSB, and 19.2% (n = 95) had adequate DPB. Householders who have ≤ 4 family members are 1.74 times (aOR = 1.74; 95% CI: 1.17 - 2.61) more likely to have adequate HSB and 1.85 times (aOR = 1.85; 95% CI: 1.11 - 3.09) more likely to have adequate DPB. The age group of 46 to 70 years' individuals (aOR = 1.74; 95% CI:1.12 - 2.92), and who engaged in employment (aOR = 1.68; 95% CI: 1.05 - 2.67) were more likely to have adequate DPB than the group of 18 to 45 years and the non-employed individuals respectively. Of them, 24.6% (n = 122) perceived that they have adequate CC. The householders who have per-capita income < USD 50 are 1.95 times (aOR = 1.95; 95%CI:1.11 - 3.40) more likely to have adequate CC. Conclusion The HSB, DPB and CC need to be improved to change the behaviour for sustainable dengue prevention and community capacity-building programmes need to be conducted in the Kurunegala district, Sri Lanka.